2015
DOI: 10.1161/circinterventions.114.002450
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Analysis of Patients With ST-Segment–Elevation Myocardial Infarction Transferred for Primary Percutaneous Intervention

Abstract: Multiple strategies have been used to improve the safety and efficacy of regional primary percutaneous coronary intervention (PCI) for ST-segment-elevation myocardial infarction (STEMI) programs. [1][2][3] Strategies that may improve first medical contact to device times include prehospital cardiac catheterization laboratory activation and bypass of non-PCI-capable hospitals or emergency departments. 4,5 Although rerouting patients directly to PCI centers may eliminate potential delays associated with transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 29 publications
(37 reference statements)
1
45
1
2
Order By: Relevance
“…Multiple contemporary studies suggest that <30% of patients in the United States meet this goal 10, 11, 12, 21, 22. One study, which limited transport time to within 60 minutes, reported that 65% of patients were treated within 120 minutes 13. However, these studies likely overestimate performance, given that high‐performing hospitals are more likely to submit data to the national registries 12, 23.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple contemporary studies suggest that <30% of patients in the United States meet this goal 10, 11, 12, 21, 22. One study, which limited transport time to within 60 minutes, reported that 65% of patients were treated within 120 minutes 13. However, these studies likely overestimate performance, given that high‐performing hospitals are more likely to submit data to the national registries 12, 23.…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation in Korea demonstrated that timely treatment for STEMI IFTs remains a challenge and is not limited to the United States 24. Lack of regional coordination and EMS use for primary transports contribute to overall delays within a STEMI system of care,13, 24, 25 whereas a coordinated system can deliver timely care over considerable distances 6, 26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been seen that door-to-balloon times have improved over time and narrowed (but not eliminated) disparity [55]. Most recently, in looking at a registry of 14,518 patients transferred from a non-PCI to a PCI center for primary PCI treatment, it was found that those with first door-to-device times greater than 120 min were 19 % more likely to be of non-white race [56]. …”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%